Systematic review of the utility of functional MRI to investigate internet addiction disorder: recent updates on resting state and task-based fMRI - Sharifat, Hamed; Abdul Rashid, Aida; Suppiah, Subapriya (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Internet addiction disorder (IAD) particularly the internet gaming disorder (IGD) is recognized as a type of addiction similar to substance abuse. This addiction carries similar social impact as the latter, as it can cause serious impairment of interpersonal relationship, and even deterioration of academic or occupational performances. Functional magnetic resonance imaging (fMRI) is able to act as a non-invasive objective biomarker to detect functional neuronal connectivity in areas of the brain affected by IAD by utilizing blood oxygenation level dependent (BOLD) imaging. Methods: A systematic review was conducted from original articles published from January 2014 to January 2017 that had the keywords “internet addiction” and fMRI. Results: Initial data collection had 170 articles, however after applying the inclusion and exclusion criteria, there were 34 articles in the final analysis (17 resting-state fMRI studies and 18 task-based fMRI studies). The striatal nucleus and dopaminergic system demonstrated impaired functioning in subjects with IAD. Conclusion: Task-based and resting-state fMRI are able to detect areas of the brain that are activated in subjects with internet addiction, similar to those observed in subjects with substance abuse and other addictions. This review also introduces a newly arising subtype which is smartphone addiction disorder.